2022
DOI: 10.3390/ijerph192114044
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices Related to Medication, Antibiotics, and Vaccination among Public Service Population: National Survey Conducted in France

Abstract: Medication, antibiotics, and immunization are three major and cost-effective medical interventions but their use is balanced. Knowledge, attitudes and practices (KAP) are a cornerstone. This retrospective study aims at analyzing KAP related to these concerns among the public service population in order to establish the basis for the implementation of selective preventive actions. From a cross-sectional anonymous online questionnaire-based survey among the insurees of a French mutual organization (Union Prévent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In 2019, VH was recognized by the World Health Organization (WHO) as one of the key threats to global health [ 1 ]. VH is a widely studied phenomenon, and is inherent to the population [ 2 , 3 , 4 ]. Compared to other parts of the world, countries in the European Union (EU) are less vaccine-confident, and there is a trend towards decreasing confidence over time [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, VH was recognized by the World Health Organization (WHO) as one of the key threats to global health [ 1 ]. VH is a widely studied phenomenon, and is inherent to the population [ 2 , 3 , 4 ]. Compared to other parts of the world, countries in the European Union (EU) are less vaccine-confident, and there is a trend towards decreasing confidence over time [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study of seven European cities recently found that polypharmacy is common among relatively healthy older adults and that factors such as being a woman, older age, a greater body mass index, and a greater number of comorbidities were associated with increased odds of polypharmacy [5]. Despite having a high level of medication knowledge, public service workers in France who used "multiple sources of trustworthy information" had increased exposure to polypharmacy, including the overuse of antibiotics and hypnotics that induce sleep [6]. The position statement of the International Group for Reducing Inappropriate Medication Use & Polypharmacy (IGRIMUP) asserts that, when prescribing without definitive benefits, "less is more" for many older adults [7].…”
Section: Introductionmentioning
confidence: 99%